2020
DOI: 10.3390/ijms21020378
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Synthetic Peptide AESIS-1 Exerts a Preventive Effect on Collagen-Induced Arthritis Mouse Model via STAT3 Suppression

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease that is associated with systemic inflammation and results in the destruction of joints and cartilage. The pathogenesis of RA involves a complex inflammatory process resulting from the action of various proinflammatory cytokines and, therefore, many novel therapeutic agents to block cytokines or cytokine-mediated signaling have been developed. Here, we tested the preventive effects of a small peptide, AESIS-1, in a mouse model of collagen-induced arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…STAT3 is activated in response to the phosphorylation of various cytokines and growth factors, such as IFN-γ, IL-5, IL-6, and LIF. A previous study reported that the novel synthetic peptide AESIS-1 could be an effective therapeutic for treating RA via the downregulation of STAT3 signaling (25). Therefore, we speculated that Jingulian may directly activate the PI3K pathway and inhibits the molecular function of STAT3 to reduce the inflammatory response.…”
Section: Discussionmentioning
confidence: 92%
“…STAT3 is activated in response to the phosphorylation of various cytokines and growth factors, such as IFN-γ, IL-5, IL-6, and LIF. A previous study reported that the novel synthetic peptide AESIS-1 could be an effective therapeutic for treating RA via the downregulation of STAT3 signaling (25). Therefore, we speculated that Jingulian may directly activate the PI3K pathway and inhibits the molecular function of STAT3 to reduce the inflammatory response.…”
Section: Discussionmentioning
confidence: 92%
“…First, we examined the effects of WKYMVm, a surrogate agonist for FPRs, on CIA according to a previous report 27 . CIA mice with vehicle showed markedly increased paw thickness and clinical scores from day 26, which were sustained up to 35 days after immunization (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…First, we examined the effects of WKYMVm, a surrogate agonist for FPRs, on CIA according to a previous report. 27 CIA mice with vehicle showed markedly increased paw thickness and clinical scores from day 26, which were sustained up to 35 days after immunization (Figure 1A ). However, administration of WKYMVm in CIA mice significantly attenuated the clinical signs of CIA, showing decreased paw swelling compared to the vehicle‐treated arthritic group (Figure 1A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…In previous research, the novel synthetic peptide AESIS-1 had preventive effects on a collagen-induced arthritis (CIA) model in mice, which is the most widely studied model of rheumatoid arthritis [33,34]. To investigate the efficacy of the AESIS-1 peptide on chronic wound repair, a diabetic wound-healing model was used in this study.…”
Section: Aesis-1 Exerted Acceleration Of Wound Healing In Vivomentioning
confidence: 99%
“…A previous study of the novel 19-amino-acid bioactive peptide AESIS-1 found it to have therapeutic activity for rheumatoid arthritis treatment [33]. Based on several reports of delayed wound-healing side effects common in rheumatoid arthritis patients [1,3] and reports that rheumatoid arthritis therapeutics can accelerate the wound-healing process [4], we conducted a study on the possibility of applying AESIS-1, an anti-RA agent, as a woundrepair therapeutic.…”
Section: Introductionmentioning
confidence: 99%